System Center 2012 Operations Manager unleashed - Meyler, Kerrie; Fuller, Cameron 1970-; Joyner, John (Sams, 2013)
This is the first comprehensive Operations Manager 2012 technical resource for every IT implementer and administrator. Building on their bestselling OpsMgr 2007 book, three Microsoft System Center Cloud and Data Center Management MVPs thoroughly illuminate major improvements in Microsoft's newest version-including new enhancements just added in Service Pack 1. You'll find all the information you need to efficiently manage cloud and datacenter applications and services in even the most complex environment. The authors provide up-to-date best practices for planning, installation, migration, configuration, administration, security, compliance, dashboards, forecasting, backup/recovery, management packs, monitoring including .NET monitoring, PowerShell automation, and much more. Drawing on decades of enterprise and service provider experience, they also offer indispensable insights for integrating with your existing Microsoft and third-party infrastructure. Detailed information on how to ... Plan and execute a smooth OpsMgr 2012 deployment or migration Move toward application-centered management in complex environments Secure OpsMgr 2012, and assure compliance through Audit Collection Services Implement dashboards, identify trends, and improve forecasting Maintain and protect each of your OpsMgr 2012 databases Monitor virtually any application, environment, or device: client-based, .NET, distributed, networked, agentless, or agent-managed Use synthetic transactions to monitor application performance and responsiveness Install UNIX/Linux cross-platform agents Integrate OpsMgr into virtualized environments Manage and author management packs and reports Automate key tasks with PowerShell, agents, and alerts Create scalable management clouds for service provider/multi-tenant environments Use OpsMgr 2012 Service Pack 1 with Windows Server 2012 and SQL Server 2012.
Includes bibliographical references and index. - Print version record
Keywords: Microsoft Windows server; Electronic data processing -- Management; Computer systems -- Evaluation; Computer networks -- Management; Systèmes informatiques; Évaluation; Réseaux d'ordinateurs; Gestion; Computer networks; Management; Computer systems; Evaluation; Electronic data processing; Management